SOCIETY, SCHOOLS AND PROGRESS IN ENGLAND (Author: G. Baron); SOCIETY, SCHOOLS AND PROGRESS IN SCANDINAVIA (Author: C. Willis Dixon); SOCIETY, SCHOOLS AND PROGRESS IN FRANCE (Author: W. D. Halls); SOCIETY, SCHOOLS AND PROGRESS IN THE U.S.A. (Author: Edmund J. King); SOCIETY, SCHOOLS AND PROGRESS IN NIGERIA (Author: L. J. Lewis); SOCIETY, SCHOOLS AND PROGRESS IN AUSTRALIA (Author: P. H. Partridge); SOCIETY, SCHOOLS AND PROGRESS IN INDIA (Author: John Sargent); SOCIETY, SCHOOLS AND PROGRESS IN CANADA (Author: Joseph Katz) - Gillett, Margaret (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1969)
G. Baron. Society, Schools and Progress in England. London: Pergamon, 1966, 228 pp., 4.50. C. Willis Dixon. Society, Schools and Progress in Scandinavia. 1965, 193 pp., 4.50. W. D. Halls. Society, Schools and Progress in France. 1965, 194 pp., 4.50. Edmund J. King. Society, Schools and Progress in the U.S.A. 1966, 241 pp., 4.50. L. J. Lewis. Society, Schools and Progress in Nigeria. 1965, 159 pp., 2.95. P. H. Partridge. Society, Schools and Progress in Australia. 1968, 246 pp., 4.00. John Sargent. Society, Schools and Progress in India. 1968, 233 pp., 4.00. Joseph Katz. Society, Schools and Progress in Canada. 1969, 148 pp., 3.50.